Comminuted Proximal Pediatric Femur Fractures Treated with External Fixation: A Case Series and Literature Review - Bicheng Yong; Anirejuoritse Bafor; Christopher Iobst (Journal of Limb Lengthening & Reconstruction)
Background: Pediatric femur fractures occur at an annual rate of 19–26 per 100,000 children, but subtrochanteric fractures remain relatively rare. The infrequency of these fractures in skeletally immature patients contributes to a lack of consensus on optimal treatment. Internal fixation is more commonly used; however, external fixation presents a minimally invasive alternative that allows for early mobilization. Methods: We present a case series of three pediatric patients who sustained closed comminuted subtrochanteric femur fractures. All patients were treated with closed reduction followed by external fixation using a modular system designed for femoral fractures. Operative time, intraoperative blood loss, alignment, and clinical outcomes were recorded. Results: All three patients underwent successful closed reduction and external fixation with short operative times and negligible blood loss. The unique femoral arch configuration and rapid adjustment struts of the fixator allowed for precise alignment control. No major complications were reported, and all patients achieved radiographic union and functional recovery without additional procedures. Conclusion: External fixation is a viable and effective treatment option for pediatric comminuted subtrochanteric femur fractures. Its minimally invasive nature, preservation of the fracture zone, and capability for fine alignment adjustment make it particularly suitable for complex fracture patterns. Further studies are warranted to compare long-term outcomes with internal fixation methods.